Numerical evaluation of Hybrid Deck Bulb Tee (HDBT) as a solution to improve durability of single-span bridges - Agüero-Barrantes, Pablo; Hain, Alexandra (Frontiers in Built Environment, 2024)
To address the shortcomings of traditional prestressed concrete girders, a new hybrid beam element, the Hybrid Deck Bulb Tee (HDBT) is proposed. The HDBT utilizes staged fabrication. First, the bottom flange is cast with Ultra-high Performance Concrete (UHPC) and prestressed prior to casting the web and top flange with High-Performance Concrete (HPC). The purpose of this study is to analytically evaluate the structural performance of HDBT beams for bridge structures. Multiple HDBT bridges were designed following the state-of-the-art criteria in regard to UHPC bridge design. The performance was evaluated using the following criteria: 1) the deflections under live load and dead load, 2) design checks for temporary stresses before losses, 3) stresses at serviceability limit states after losses, and 4) demand-to-capacity ratios under the American Association of State Highway and Transportation Officials (AASHTO) Strength I load combination. To obtain more refined results for the serviceability limit state, the bridges were modeled using a commercial finite element software. The model captured the time dependent material properties such as strength gain, creep, and shrinkage, as well as the stages of fabrication. The analysis demonstrates that the innovative design and fabrication processes of HDBTs are capable of resolving the current limitations of prestressed concrete elements.